PENGARUH EKSTRAKULIKULER TAHFIZ AL-QUR’AN TERHADAP HASIL BELAJAR AL QUR’AN HADIST KELAS III MI NW 01 KEMBANG KERANG - Kikah, Ulfa Nurhakikah (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2022)
This study aims to determine the effect of extracurricular Tahfiz Al-Qur'an on learning outcomes Al-Qur'an Hadith class III MI NW 01 Kembang Kerang. The method used is quantitative comparative design. The independent variable is the extracurricular Tahfiz Al-Qur'an and the dependent variable is the result of learning the Al-Qur'an Hadith. The sample used was a random sampling technique (Simple Random Sampling) in this study were students of class III A MI NW 01 Kembang Kerang. Data collection was carried out by means of documentation and oral tests as the main data source and interviews as additional data sources, while the data analysis technique used was simple linear regression and product moment. The results showed that the memorization results of students in class III A MI NW 01 Kembang Kerang obtained an average score of 49.5 while the learning outcomes of the Al-Qur'an Hadith students of class III A MI NW 01 Kembang Kerang obtained an average value of 63.9. Based on the calculation of the correlation coefficient at the 5% level with > or 0.64 > 0.381, the hypothesis is accepted. This means that the average value of Al-Qur'an Hadith class III A MI NW 01 Kembang Kerang learning outcomes is 40.96% determined by the Extracurricular Tahfiz Al-Qur'an which is given through the regression equation Y = 43 + 0.42X. while the remaining 59.04% is determined by other factors